1973
DOI: 10.1172/jci107216
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia: Influence on Lung Mechanics and Protein Synthesis

Abstract: A B S T R A C T We studied the time-course of the influence of in vivo hyperoxia on lung mechanics and on protein synthesis. After 24 h of exposure to greater than 98% 02 at 1 atm there were no alterations in descending pressure-volume curves (air or saline) of lungs excised from O2-exposed rats compared to control rats. After 48 h of hyperoxia there was a decrease in lung compliance.To study protein synthesis, as indicated by L-[U-'4C] leucine incorporation into protein, lung slices were incubated with L-[U-J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 23 publications
(18 reference statements)
2
19
0
Order By: Relevance
“…The present work has shown that the size of lamellar bodies of rats exposed to hyperoxia for 48 h are smaller Hyperoxia decreased the incorporation of ["4C]leucine into protein in a surface-active lung fraction (7), to about the same extent as the decrease in lamellar body size. Thus, it would appear that in the face of a hyperoxia-induced decrease in synthesis of secretory protein the "packages" for export are smaller.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The present work has shown that the size of lamellar bodies of rats exposed to hyperoxia for 48 h are smaller Hyperoxia decreased the incorporation of ["4C]leucine into protein in a surface-active lung fraction (7), to about the same extent as the decrease in lamellar body size. Thus, it would appear that in the face of a hyperoxia-induced decrease in synthesis of secretory protein the "packages" for export are smaller.…”
Section: Discussionsupporting
confidence: 52%
“…We have shown that incorporation of [14C]leucine into protein of a surface active lung fraction, is decreased after in vivo exposure of rats to hyperoxia (7). These considerations make it reasonable to suspect that the decreased incorporation of [14C]leucine into protein of the surfaceactive lung fraction in rats exposed to hyperoxia might be reflected in alterations in the size, number, or both of these storage sites.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Received for publication 30 July 1973 and in revised form 12 November 1973. protein synthesis by lung (1). The decrease in the synthesis of protein in a surface-active fraction is greater than the decrease in synthesis of protein in the whole lung homogenate.…”
Section: Introductionmentioning
confidence: 92%
“…METHODS Animals. We used Dublin-Sprague Dawley-derived male rats (Flow Research Animals Inc., Dublin, Va.) weighing between 100-125 g. They were exposed to oxygen (> 98%o) or compressed air and sacrificed as previouslydescribed (1).…”
Section: Introductionmentioning
confidence: 99%